The Effect of Public Information Systems Implementations on Public Transparency - Ignasius Grendo K Panggabean; Annisa Putri; Muhammad Mahardika Chandra; Putri Najwa Amalia; Willy Febrian Sipayung; Galih Supraja (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the impact of the implementation of Public Information Systems (SIP) on public transparency in government. By utilizing information technology, SIP is designed to increase openness, accountability, and public participation in the decision-making process. The study was conducted using a literature study method by reviewing various relevant scientific sources, including journals, books, and official documents. The results of the study indicate that the implementation of SIP significantly contributes to increasing information transparency, service efficiency, and public trust in the government. However, several obstacles were found, such as limited technological infrastructure, gaps in internet access in remote areas, and low digital literacy in the community. This study recommends strengthening technological infrastructure, increasing human resource capacity, and digital literacy education as strategic steps to optimize the implementation of SIP. With these steps, SIP can be an effective solution to support more inclusive and transparent electronic-based governance.